An evaluation of patient safety culture in a secondary care setting in Kuwait. Issue 3 (June 2018) - Alqattan, Hamad; Cleland, Jennifer; Morrison, Zoe
الملخص: أهداف البحث: يعتبر خلق ثقافة سلامة المرضى الإيجابية أساسا لتحسين نتائج سلامة المرضى. تهدف هذه الدراسة لإجراء التقييم الأول لثقافة سلامة المرضى في محيط الرعاية الثانوية في الكويت. طرق البحث: أجريت هده الدراسة الاستطلاعية –المقطعية في القسم الطبي في مستشفى عام في الكويت باستخدام مسح لثقافة سلامة المرضى في المستشفى. وتم عمل تحليل الانحدار الخطي المتعدد لتحديد توقعات ثقافة سلامة المرضى. تم استخدام كلا من اختبار أنوفا وكروسكال واليس لتقييم الاختلافات بين مجموع الدرجات والدرجات التي تم تحقيقها في كل بُعدٍ حسب ترتيب الجنسيات. النتائج: تم استلام ١٠٠٨ استبانة مكتملة، بمعدل استجابة ٧٥.٢٪. وجدنا ثلاثة أبعاد لثقافة سلامة المرضى لتكون مجالات ذات أولوية للتحسين: استجابة غير- عقابية للأخطاء، والتوظيف، وانفتاح التواصل. تم تحديد العمل الجماعي داخل الوحدات والتعليم التنظيمي مع التحسين المستمر كمجالات للقوة. كان لدى الذين استجابوا من الكويت⁄ دول الخليج إيجابية أقل لثقافة سلامة المرضى بالمقارنة بالمستجيبين الآسيويين. وأظهر تحليل الانحدار للمستجيبين أن" بلد المنشأ "، والمهنة، والعمر والحضور لدورات ⁄ محاضرات ثقافة سلامة المرضى كانت مرتبطة ارتباطا كبيرا لإدراك ثقافة سلامة المرضى. الاستنتاجات: أظهرت هذه الدراسة أن سلامة المرضى ينظر إليها بشكل مختلف بين الطاقم الطبي من مختلف بلدان المنشأ، والمجموعات المهنية، والفئات العمرية. يجب الإقرار بهذه المتغيرات ومعالجتها عند تخطيط وتقييم مبادرات سلامة المرضى. Abstract: Objectives: To improve patient safety outcomes, it is considered essential to create a positive culture of patient safety. This study carried out an initial evaluation of the patient safety culture in a secondary care setting in Kuwait. Methods: This cross-sectional questionnaire study was conducted in a general hospital medical department in Kuwait, using the Hospital Survey on Patient Safety Culture (HSPSC). Multiple linear regression analyses were used to identify patient safety culture predictors. Both an ANOVA and a Kruskal Wallis test were carried out to assess the differences between participants' total scores and the scores they achieved in each dimension, categorized by nationality. Results: A total of 1008 completed questionnaires were received, yielding a response rate of 75.2%. Three dimensions of patient safety culture were found to be priority areas for improvement: non-punitive responses to errors, staffing, and communication openness. Teamwork within units and organizational learning with continuous improvement were identified as areas of strength. Respondents from Kuwait and the Gulf State countries had a less positive perception of the hospital's patient safety culture than did Asian respondents. A regression analysis showed that the respondents' countries of origin, professions, age, and patient safety course/lecture attendance were significantly correlated with their perceptions of the hospital's patient safety culture. Conclusion: This study demonstrates that patient safety is perceived differently by medical staff members from different countries of origin, professional groups, and age groups. These variables must be acknowledged and addressed when planning or evaluating patient safety initiatives.